Characterization of the E2 gene of classical swine fever virus (CSFV) isolated in Vietnam - Thanh Huong, Doan Thi; Thi Khue, Nguyen; Roan, Do Thi; Thu Hien, Nguyen Thi; Minh Duc, Luu; Thi Hue, Le; Khanh Linh, Pham Thi; Kim Xuyen, Le Thi; Hai Ngan, Doan; Xuan Doc, Phan (Academia Journal of Biology, 2025)
Classical swine fever is one of the most dangerous infectious diseases, causing significant economic damage to the pig industry globally and in Vietnam. The disease is caused by the Classical Swine Fever Virus (CSFV), an RNA virus with a high mutation rate. Classical swine fever remains a complex and persistent threat. In this study, the full E2 gene of CSFV strains collected from Ha Noi (21.028333 N, 105.853333 E), Da Nang (16.079 N, 108.217 E), and Quang Ninh (21.250982 N, 107.193604 E) was analyzed alongside three vaccine strains currently used in Vietnam. The results show that the highly virulent CSFV strains circulating in 2023 belong to genotypes 1.1, 2.1, and 2.2, while the vaccine strains in use belong to genotype 1.1. There are notable differences in amino acids at key antigen epitope sites between the vaccine strains and the circulating CSFV strains in 2023. These findings highlight the need to develop new vaccines that are better suited to the currently circulating virus strains.